Lifestyles of adolescents and their relationship with the perception of their development contexts - Campos-Valenzuela, Noemí (Universidad de Sonora, 2023)
Introduction: Although lifestyles are generated and consolidated in adolescence, when these lifestyles are unhealthy, adolescents expose themselves to health risks. Objective: Identify the lifestyles of adolescents and its relationship with the perception of their development contexts. Methodology: A descriptive study was used, with bivariate analysis of comparison of means and correlation, carried out on a sample of 489 adolescents aged 10 to 19 years old from public schools of Biobío, Chile, excluding adolescents with cognitive deficits and/or sense organ disorders. Ethical aspects considered parental consent and the agreement from every adolescent. The "FANTÁSTICO" instrument, adapted Chilean version was used, which measures 8 dimensions related to health, mental wellbeing and perception, family affective relationships, and school environment. The analyses were descriptive and correlational. Results: Almost half of the sample reported lifestyles that require changes and/or interventions. The youngest ones showed healthier lifestyles with differences by sex. Healthy behaviors had a statistically positive relationship to mental well-being and to the perception of their developmental contexts such as family affective relationships and their school environment. Conclusions: The findings support the design of future intervention studies that consider early adolescent ages and differences by sex, especially aimed at improving the closest developmental contexts such as family, schools, and their neighborhoods.